On the Other Hand: Nondominant Hand Use Increases Sense of Agency. (August 2014) - Damen, Tom G. E.; Dijksterhuis, Ap; Baaren, Rick B. van
In two studies, we investigated the influence of hand dominance on the sense of self-causation or agency. Participants alternately used their dominant or nondominant hand to cause the occurrence of an effect (a tone) in a task in which agency was made ambiguous. Participants were subsequently asked to indicate the degree to which they felt they had caused that tone to occur. Results showed that the sense of agency was increased when individuals used their nondominant hand prior to the onset of the tone, compared to when they used their dominant hand. Furthermore, the degree of experienced agency was moderated by perceived effort. The difference in agency levels occurred independently of experimentally induced or naturally occurring differences in response latencies and even occurred in the absence of (major) arm movement.